ABOUT THE PATHOGENETIC BASIS, FEATURES OF THE CLINICAL COURSE AND THE SELECTIVE APPROACH TO THE SELECTION OF INTERVENTION DEPENDING ON THE PHASES OF THE CLINICAL COURSE OF PERSISTENT TRAUMATIC SUBDURAL HYDROMAS (World Science, 2023)
The work is based on an analysis of surgical treatment of 57 victims with a persistent form of traumatic subdural hydromas. The pathogenetic basis and features of the clinical course of persistent hydromas and their neurological symptoms were clarified. The often observed phasic nature of the clinical course of persistent subdural hydromas has been noted; describes neurological symptoms characteristic of the transition from the pure, uncomplicated phase of subdural hydromas to the complicated, persistent clinical phase. Using the method of in-depth analysis of intraoperative surgical findings and clinical observations of neurological signs, the dependence of the pathoanatomical states of the brain on the prolonged compressive influence of volumetrically accumulating fluid in the subdural cavity was established. It is clarified that the persistent clinical form more often occurs with inertial injuries and with the valve mechanism of hydroma formation. It has been established that pure, uncomplicated traumatic subdural hydromas occur in 4-5% of cases among various clinical and anatomical forms of severe traumatic brain injury. Among them, in 31.5% of cases, pure, uncomplicated subdural hydromas take on a protracted clinical course - they become severe, persistent phase (in 57 cases among 181 of our observations) with frequent death - in 24 (42.1%) cases among 57 cases of complicated, persistent forms of traumatic subdural hydromas. Based on significant clinical material (57 observations), it was established that in the persistent clinical phase, the only indication is osteoplastic craniotomy with intraoperative straightening of the collapsed brain by injection into the lateral ventricle, through the inferior horn, up to 10-15 ml. distilled solution or 20-25 cc. air with the creation at the end of the intervention of additional, subapponeurotic reserve spaces, by detaching the apponeurotic skin flap from the periosteum of the skull around the burr hole, to a depth of 10-15 cm, for the “waste” of the cerebrospinal fluid collecting in the subdural cavity, in order to prevent conditions for mass the effect of compression and dislocation of the brain. Along with the indicated innovative surgical method, it is recommended that, in order to improve volumetric cerebral blood flow and enhance brain perfusion, resuscitation measures include means that enhance the left ventricular volumetric output of blood. In the case of a complicated, persistent form of subdural hydromas, repeated intervention should be strongly preferred to the microcraniotomy method, expectant management and prolonged resuscitation measures, including forced dehydration therapy.